Evolving Corporate Governance in Indian Healthcare: An Ethical Perspective - Chebolu, Dr. Radha Mohan; Saravanan, D. (The journal of contemporary issues in business and government, 2021)
The ongoing trends in the Indian healthcare sector point to the need to evolve a strategic plan with concern towards ‘quality care’. This demands a massive governance agenda from a management perspective. The evolution of Corporate Hospitals, on a mammoth scale, across the country heralded a new era in the realm of ‘diagnosis’ and ‘treatment’ unfolding many technologies. The so-called boom in the service sector, found to be responsible for elevating the living standards of the middle class, needs to be channelised for a productive cause. The growing awareness of health disorders and treatment-seeking attitude among the cross section of people put enormous pressure on corporate hospitals to prescribe an action plan for meeting customer needs spread in different forms. The entry of foreign capital into the fold of healthcare services has also resulted in a competition between equal players as seen in the case of heart ailments. The individual-centric and group-centric management patterns found in the corporate hospitals require a healthy debate on the pros and cons of the phenomenon. The growing thrust towards ‘quality management’ also enables us to focus upon ‘clinical governance’ that finds special place in the so-called corporate governance framework. Apart from this, technological implications and the resulting cost escalation are identified as potential elements that need attention in the effective management of corporate hospitals. The journey from ‘commercialization’ to ‘corporatization’ in varying forms has been analyzed. Above all, the classic models of management followed in Banking, Finance and IT sectors, which came to be known as ‘Corporate Governance’ is being thrust upon corporate hospitals for implementation in view of its positive outcome elsewhere. Eventually, the management architecture involves the application of an ‘ethical code of conduct’ not only for gaining the investor’s trust but also for enhancing the ‘brand image’ of the hospitals. The focus on customer-related issues be it ‘cost’ or ‘service’, at this crucial juncture would ensure a fair balance between business objectives and service delivery from a customer perspective. For driving corporate healthcare services towards ‘zero tolerance’ to ‘medical errors’ the pursuit of corporate governance practices seems to be imperative both from organizational and social perspectives. The blue print prepared by ‘McKinsey’ for evolving a new health policy deserves to be given adequate attention while making policy overtures across the realm of corporate hospitals.